Stress in Regulation of GABA Amygdala System and Relevance to Neuropsychiatric Diseases - Jie, Fan; Yin, Guanghao; Yang, Wei; Yang, Modi; Gao, Shuohui; Lv, Jiayin; Li, Bingjin (Frontiers in Neuroscience, 2018)
The amygdala is an almond-shaped nucleus located deep and medially within the temporal lobe and is thought to play a crucial role in the regulation of emotional processes. GABAergic neurotransmission inhibits the amygdala and prevents us from generating inappropriate emotional and behavioral responses. Stress may cause the reduction of the GABAergic interneuronal network and the development of neuropsychological diseases. In this review, we summarize the recent evidence investigating the possible mechanisms underlying GABAergic control of the amygdala and its interaction with acute and chronic stress. Taken together, this study may contribute to future progress in finding new approaches to reverse the attenuation of GABAergic neurotransmission induced by stress in the amygdala.